COI data from: Invasive species detection along coastal harbours in northern region of Vastra Gotaland 2024 - Eivind Stensrud (GBIF Sweden, 2025)
Environmental DNA sequence data of invasive species along the harbors in the northern regions of Vastra Gotaland. Sequence data was obtained from both water samples, and plankton samples of two sampling events, one in the summer and one in the autumn of 2024. The amplicons were amplified by COI Leray-XT primers: Wangensteen et al. 2018 and annotated against an inhouse database of invasive and non-indigenous species of Norway, Sweden and EEA created with EchoPipe: Stensrud et al. in press. The data was created for Länsstyrelsen Vastra Gotaland and financed through HaV.

This dataset was published via the SBDI ASV portal. (https://asv-portal.biodiversitydata.se/)
Keywords: metabarocing; alien species; NIS; eDNA; Occurrence; invasive species; Observation; OCCURRENCE; Biological Sciences; Biologi